(Gordon E. Moore Medal for Outstanding Achievement in Solid State Science and Technology Address) Transient Polymers for Low-k Dielectrics and Vaporizing Devices. (26th April 2017) - Kohl, Paul A
Abstract : Low ceiling temperature, thermodynamically unstable polymers can be used as transient polymers in the fabrication of vaporizing devices, such as sensors. However, they have been troublesome to synthesize and keep stable during storage. In this study, stable polyphthalaldehyde has been synthesized with a BF3 -OEt2 catalyst. The role of BF3 in the polymerization is described. The interaction of BF3 with the monomer is described and used to maximize the yield and molecular weight of polyphthalaldehyde. Various Lewis acids were used to investigate the effect of catalyst acidity on polyphthalaldehyde chain growth. In-situ NMR was used to identify possible interactions formed between BF3 and phthalaldehyde monomer and polymer. The molecular weight of the polymer tracks with polymerization yield. The ambient temperature stability of polyphthalaldehyde was investigated and the storage life of the polymer has been improved.